L-Glutamate Oxidase Enzyme from Hypocrea jecorina: Production and Biochemical Characterization - Eynur, Fatih Mehmet; Karakus, Emine (CHEM SOC PAKISTAN, 2014)
L-Glutamate oxidase (LGOX; EC 1.4.3.11) is the important enzyme that catalyzes the deamination of L-glutamic acid to 2-oxo glutarate and ammonium ions. In this study, the microbial production of L-glutamate oxidase enzyme from Hypocrea jecorina pure culture was carried out and the optimum conditions and calculation of some kinetic parameters of the produced enzyme were also determined by using Nesslerization reaction. The enzyme shows maximum activity at pH 8.5 and 40 degrees C in TRIS buffer. The kinetic parameters of the enzyme, K-M and Vmax values, were determined as 2.58 mM and 83.33 U/mg protein, respectively. The inactivation rate constants and half life (t(1/2)) were determined from the slope of thermal stability plots of the enzyme at 60, 70 and 80 degrees C temperatures. The activation energy (Ea) was found to be 1.40 kcal mol(-1)
Keywords: Glutamate oxidase; Hypocrea jecorina; Enzyme production; L-glutamate; Nessler reagent; FLOW-INJECTION ANALYSIS; PURIFICATION; BIOSENSOR; ELECTRODE; ACID; Chemistry